2015
DOI: 10.1016/j.envres.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Case study: Possible differences in phthalates exposure among the Czech, Hungarian, and Slovak populations identified based on the DEMOCOPHES pilot study results

Abstract: Some differences were observed between countries in the concentrations of individual urinary phthalate metabolites in children. However, the questionnaire results give no direct explanation for the differences between the countries except the variation in using personal care products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
12
1
1
Order By: Relevance
“…The geometric mean concentrations of MBzP and MEHP were higher in our study than were reported for 117 women from the Czech Republic (4.35 and 3.13 μg/g creatinine, respectively), 125 women from Slovakia (3.81 and 3.22 μg/g creatinine, respectively), and 115 women from Hungary (3.82 and 3.70 μg/g creatinine, respectively) ( Černá et al, 2015 ). In contrast, levels of MEOHP and MEHHP were lower in our study, than reported for Czech (11.68 and 18.45 μg/g creatinine, respectively), Slovakian (11.54 and 18.20 μg/g creatinine, respectively), and Hungarian (10.37 and 15.54 μg/g creatinine, respectively) women ( Černá et al, 2015 ). Overall, the distribution of exposures among our study population was unique, yet we identified similarities with values reported for several nearby, non-clinical European populations.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The geometric mean concentrations of MBzP and MEHP were higher in our study than were reported for 117 women from the Czech Republic (4.35 and 3.13 μg/g creatinine, respectively), 125 women from Slovakia (3.81 and 3.22 μg/g creatinine, respectively), and 115 women from Hungary (3.82 and 3.70 μg/g creatinine, respectively) ( Černá et al, 2015 ). In contrast, levels of MEOHP and MEHHP were lower in our study, than reported for Czech (11.68 and 18.45 μg/g creatinine, respectively), Slovakian (11.54 and 18.20 μg/g creatinine, respectively), and Hungarian (10.37 and 15.54 μg/g creatinine, respectively) women ( Černá et al, 2015 ). Overall, the distribution of exposures among our study population was unique, yet we identified similarities with values reported for several nearby, non-clinical European populations.…”
Section: Discussioncontrasting
confidence: 72%
“…However, the geometric mean total urine arsenic value for 4,730 Germans aged 18–69 (3.1 μg/g) was substantially lower than for women in our study ( Becker et al, 2003 ). In our study, we determined urinary metabolites of DBP, BzBP, and DEHP as those phthalates most prevalent in Central and Eastern European populations ( Černá et al, 2015 ). The highest urinary phthalates values in our study population were measured for MBP, MBzP, MEHP and MEHHP, while MEHP had the highest geometric mean.…”
Section: Discussionmentioning
confidence: 99%
“…Human biomonitoring on a. European Scale) study, our results were rather low compared to other Western European Countries [ 17 ]. Furthermore, data from Eastern European countries [ 18 ] also showed higher phthalate concentrations. On the other hand, our results were comparable to findings in Denmark (sampling period 2011) [ 19 ] and from another Austrian study (sampling period 2010/2012) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…1), ale přesto ani u jednoho vzorku nepřesáhly zdravotně významné hodnoty stanovené taktéž německou Komisí pro biomonitoring pro součet obou metabolitů (750 μg/l pro běžnou dospělou populaci, 300 μg/l pro ženy v reprodukčním věku). Pro dětskou populaci byla stanovena zdravotně významná limitní hodnota 500 μg/l (15,16). …”
Section: Diskuseunclassified